Analisis Literasi Digital di Era Masa Kini - Leni suciati; Sugiarti Sugiarti; Mega Wahyu Lestari; Nessy Nessy (Journal Innovation In Education, 2025)
The rapid development of digital technology has simplified access to information, yet students' digital literacy remains limited. This study aims to analyze the level of digital literacy among university students using a literature review approach. Findings reveal that while students are technically skilled in using digital tools, they often lack critical thinking, information filtering, and awareness of digital ethics and security. Internet use is still largely entertainment-focused rather than academic. Factors influencing digital literacy include media usage intensity, academic achievement, reading habits, and family support. Strengthening digital literacy through integrated education is essential to help students adapt to technological changes and face global challenges.